Evaluating the Design of a Comprehensive Nordic Hospital at Home Education–A Study Protocol - Persson, Magnus C. ; 0000-0003-1062-2789; Svane, Jeff Kirk; Grøndahl, Vigdis Abrahamsen; Grønlien, Heidi Kristine; Åvik Persson, Helene; Martinussen, Mie Hjort; Lynghøj Nielsen, Thyge; Malmgren Fänge, Agneta ; 0000-0002-3165-1856 (Advances in Medical Education and Practice, 2025)
This study protocol outlines the test evaluation of the design of a comprehensive Nordic hospital at home (HaH) digital education program entitled “the Nordic Digital Health and Education” program (NorDigHE). The NorDigHE program aims to prepare healthcare professionals for healthcare provision in a HaH context. The program, developed by a Nordic consortium, spans five modules over 3.5 weeks of full-time study, equivalent to 5 ECTS, and employs various learning tools, eg, text, videos, learning games, and simulations. The design evaluation will involve 120 healthcare students and professionals across Denmark, Norway, and Sweden, focusing on their perceptions and experiences with the different educational tools utilized in the education. To be included in the study, the participants need to have completed at least four semesters of bachelor level studies in medicine, nursing or other registered healthcare professions. Each of the participants will test two of the five modules at their own pace during the design evaluation. Evaluation data will be collected through established instruments measuring student motivation, quiz functionality, videos’ effectiveness, and the educational platform’s usability assessments. The outcomes of this study will be used to refine the education and the learning tools employed. Ultimately, the results will help optimize the structure and contents of the NorDigHE education program, to better prepare healthcare professionals and students with essential skills to navigate the evolving landscape of digital health and remote patient healthcare effectively.
Publisher Copyright: © 2025 Persson et al.
Keywords: care; digital; healthcare; hospital at home; professional; training